Optical band gap and thermal diffusivity of polypyrrole-nanoparticles decorated reduced graphene oxide nanocomposite layer - Sadrolhosseini, Amir Reza; Abdul Rashid, Suraya; Muhammad Noor, Ahmad Shukri; Kharazmi, Alireza; Lim, Hong Ngee; Mahdi, Mohd. Adzir (Hindawi Publishing Corporation, 2016)
A polypyrrole-nanoparticles reduced graphene oxide nanocomposite layer was prepared using electrochemical method. The prepared samples were characterized using Fourier transform infrared spectroscopy, field emission scanning electron microscopy, and UV-visible spectroscopy. The band gap of nanocomposite layers was calculated from UV-visible spectra and the thermal diffusivity of layers was measured using a photoacoustic technique. As experimental results, the optical band gap was in the range between 3.580 eV and 3.853 eV, and thermal diffusivity was increased with increasing the layer thickness from 2.873 cm2/s to 12.446 cm2/s.